Prenatal protein depletion and Δ9, Δ6 and Δ5 desaturases in the rat - Mercuri, Osvaldo Francisco (1979)
Pregnant rats were kept throughout gestation on a control diet (i.e., 25% protein), on a low protein diet (i.e., 5% protein) or on a fat-free diet. At 20-21 days of gestation, the rate of 9-, 6-, and 5-desaturation was measured, using microsomes from maternal and fetal livers and placenta microsomes. The effect of protein malnutrition was more evident upon Δ6-desaturase activity from maternal liver, while a less severe reduction in the activities of Δ9- and Δ5-desaturases was observed. No measurable activities of Δ5- and Δ6-desaturases were observed in fetal liver and placenta, while a low activity of Δ9-desaturase was detected in both tissues from the three groups under study. We concluded that Δ6-desaturation is greatly affected by maternal protein deprivation, and this fact could affect the normal supply of polyunsaturated fatty acids for the normal fetus growth and tissue development.